The Independent Prognostic Effect of Lymph Node Dissection on Patients With Stage IA NSCLC With Different T Stages - Zhao, Dechang; Zhang, Rusi; Yang, Longjun; Huang, Zirui; Lin, Yongbin; Wen, Yingsheng; Zhang, Xuewen; Wang, Gongming; Guo, Guangran; Yu, Xiangyang; Wang, Weidong; Xi, Kexing; et al. (Frontiers in Surgery, 2021)
Background: Currently, the extent of lymph node evaluation necessary for patients with early-stage non-small-cell lung cancer (NSCLC) remains controversial according to the latest ESMO and NCCN guidelines. In this study, we aimed to evaluate the survival effect of different numbers of lymph nodes examined (LNE) and regions of lymph nodes removed (LNR) in patients with stage IA NSCLC. Method: All patients with stage IA NSCLC undergoing lobectomy or bilobectomy were selected from the surveillance, epidemiology, and end results (SEER) database. The number of LNE and LNR were stratified into 4 groups (0, 1–2, 3–8, and ≥9 lymph nodes) and 3 groups (0, 1–3, and ≥4 regions) respectively. Additionally, the survival curves of overall survival (OS) and cancer-specific survival (CSS) were plotted and compared with the Kaplan-Meier method and log-rank test. Independent prognostic clinicopathological factors were evaluated via Cox proportional hazard regression and subgroup analysis. Results: Totally, 12,490 patients with stage IA NSCLC were enrolled in our study. Patients with ≥9 LNE and ≥4 LNR in both the T1b and T1c stages consistently demonstrated the significantly best OS and CSS outcomes. In the multivariate analysis, patients with ≥9 LNE consistently had a significantly better CSS [hazards ration (HR) (95% CI):0.539 (0.438–0.663)], and those with ≥4 LNR consistently had a significantly better OS [HR (95% CI):0.678 (0.476–0.966)]. Furthermore, ≥9 LNE and ≥4 LNR were associated with better survival in most subgroups. Conclusion: This study demonstrated that ≥9 LNE and ≥4 LNR are highly recommended for stage IA2 and stage IA3 patients but optional for stage IA1 patients.